Ligand-to-Metal Ratio Governs Radical-Scavenging Ability of Malate-Stabilised Ceria Nanoparticles - Arina D. Filippova; Alexander E. Baranchikov; Maria A. Teplonogova; Irina V. Savintseva; Anton L. Popov; Vladimir K. Ivanov (Nanomaterials)
Cerium dioxide sols stabilised with L-malic acid were shown to exhibit significant antioxidant activity towards alkyl peroxyl radicals in the range of ligand:CeO2 molar ratios of 0.2–1 (0.2:1, 0.4:1, 0.5:1, 0.6:1, 0.8:1 and 1:1). The antioxidant activity of cerium dioxide nanoparticles greatly depended on L-malic acid content and increased by 8 times when the ligand:CeO2 molar ratio increased from 0.2:1 to 0.4:1. An estimate of the ligand:CeO2 molar ratio required to ensure complete surface coverage of CeO2 nanoparticles with malate anions resulted in a value of 0.2. Aggregation degree of CeO2 nanoparticles depends on the ligand:CeO2 molar ratio. In the range of ligand:CeO2 molar ratios 0.2–0.4, the size of aggregates decreased by an order of magnitude. The antioxidant capacity of 1 mM malate-stabilised cerium dioxide (0.2:1) relative to sodium ascorbate was 0.012 ± 0.001 mM. The antioxidant activity of cerium dioxide stabilised with L-malic acid at a ligand:CeO2 molar ratio of 0.2:1 was 80 times less than the antioxidant activity of sodium ascorbate. Cerium dioxide nanoparticles stabilised with L-malic acid did not demonstrate a cytotoxic effect against human mesenchymal stem cells, in a wide range of concentrations (10−3–10−5 M), and their proliferation was stimulated after 72 h of cultivation. The results obtained show new possibilities for the design of biocompatible ceria-based nanomaterials with tunable pro- and antioxidant properties; these materials can further be assessed in view of their potential for treating oxidative stress-related disorders.